2016
DOI: 10.1039/c6dt03106d
|View full text |Cite
|
Sign up to set email alerts
|

An unusual assembled Pb(ii) meso-helicate that shows the inert pair effect

Abstract: A dinuclear Pb(ii) mesocate has been prepared with an unprecedented four-coordinated kernel in which the Pb(ii) lone pair is stereochemically active. This is the first time that this effect has been observed in a supramolecular Pb(ii) helicate or meso-helicate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The occurrence of argentophilic interactions may result in peculiar arrangements of the counterions, columnar for example, that themselves may induce novel architectures of the anionic uranyl-containing polymer . Another metallic cation displaying irregular coordination geometries and highly variable coordination numbers, ranging from 2 to 10, is lead­(II), which has not often been used in association with uranyl cations. ,,, The possible but controversial effects of the lead­(II) lone pair on its coordination preferences adds further interest to such a study. The reported uranyl–silver­(I) complexes with carboxylate ligands involve acetate, pimelate, benzene-1,4-dicarboxylate, 1,3,5-benzenetriacetate, 1,4-naphthalenedicarboxylate, isonicotinate, 2,6-pyridinedicarboxylate, tetrahydrofurantetracarboxylate, and 2,5-thiophenedicarboxylate, while known uranyl–lead­(II) species contain acetate, 2,6-pyridinedicarboxylate, 1,3,5-benzenetriacetate, and tetrahydrofurantetracarboxylate, these four ligands being thus represented in both series.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of argentophilic interactions may result in peculiar arrangements of the counterions, columnar for example, that themselves may induce novel architectures of the anionic uranyl-containing polymer . Another metallic cation displaying irregular coordination geometries and highly variable coordination numbers, ranging from 2 to 10, is lead­(II), which has not often been used in association with uranyl cations. ,,, The possible but controversial effects of the lead­(II) lone pair on its coordination preferences adds further interest to such a study. The reported uranyl–silver­(I) complexes with carboxylate ligands involve acetate, pimelate, benzene-1,4-dicarboxylate, 1,3,5-benzenetriacetate, 1,4-naphthalenedicarboxylate, isonicotinate, 2,6-pyridinedicarboxylate, tetrahydrofurantetracarboxylate, and 2,5-thiophenedicarboxylate, while known uranyl–lead­(II) species contain acetate, 2,6-pyridinedicarboxylate, 1,3,5-benzenetriacetate, and tetrahydrofurantetracarboxylate, these four ligands being thus represented in both series.…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, we published the first case of a helicate/mesocate showing the inert pair effect: a Pb­(II) hydrazone mesocate with a low coordination number . A detailed study of this mesocate indicated that the lead lone pair may prevent the ligands from crossing and therefore prevents the formation of a metallohelicate.…”
Section: Resultsmentioning
confidence: 99%
“…In 2016, we published the first case of a helicate/mesocate showing the inert pair effect: a Pb(II) hydrazone mesocate with a low coordination number. 29 A detailed study of this mesocate indicated that the lead lone pair may prevent the ligands from crossing and therefore prevents the formation of a metallohelicate. For that reason, we believe that the stereochemically active Pb(II) lone pair must be considered as an important factor that determines the assembly of Pb(II) mesocates versus helicates.…”
Section: Inorganic Chemistrymentioning
confidence: 99%
“…4) where Pb 2+ shows no thiophilicity at all. Pb 2+ The reason for the unexpected property indicated above, relating to different S sites, is most likely the 6s 2 lone pair 13,86,87 of Pb 2+ which may give rise to a hemidirected structure as observed, e.g., for the complex Pb2(L)2, where L is the dianion of bis-salicyloylhydrazone and where Pb(II) is coordinated by two N and two negatively charged O sites, 88 with the result that the vacant part (cf. also Ref.…”
Section: Conclusion Including the Role Of The Lead(ii) Lone Pairmentioning
confidence: 91%
“…86) of the coordination sphere of Pb 2+ is occupied by the lone pair. 88 Clearly, the stereochemically active 6s 2 lone pair cannot remain in a s-orbital if it is to produce an asymmetric coordination sphere. 89 Depending on whether the 6s 2 lone pair causes a spherical or a non-spherical charge distribution around Pb(II), the geometry of the complexes is symmetric or distorted.…”
Section: Conclusion Including the Role Of The Lead(ii) Lone Pairmentioning
confidence: 99%